Prognostic Role of Neutrophil to High-Density Lipoprotein Cholesterol Ratio for All-Cause and Cardiovascular Mortality in the General Population - Jiang, Ming; Sun, Jinyu; Zou, Huayiyang; Li, Menghuan; Su, Zhenyang; Sun, Wei; Kong, Xiangqing (Frontiers in Cardiovascular Medicine, 2022)
Background Neutrophil counts to high-density lipoprotein cholesterol ratio (NHR), a composite marker of inflammation and lipid metabolism, has been considered as a predictor of clinical outcomes in patients with acute ischemic stroke and acute myocardial infarction. However, the predictive value of NHR for all-cause and cardiovascular mortality in the general population remain unclear. Methods Our population composed of 34335 adults in the United States obtained from National Health and Nutrition Examination Survey 1999-2014 and grouped in accordance with tertiles of NHR. Kaplan-Meier curves and long-rank test were used to investigate the differences of survival among groups. Multivariate Cox regression, restricted cubic spline analysis and subgroup analysis was applied to explore the relationship of NHR with all-cause and cardiovascular mortality. Results In a total of 34, 335 participants, mean age was 49.6 ± 18.2 years and 48.4% were male. During a median follow-up of 82 months, 4310 (12.6%) all-cause deaths and 754 (2.2%) cardiovascular deaths occurred. Compared with lowest tertile, the highest NHR tertile was significantly associated with all-cause and cardiovascular mortality with an adjusted hazard ratio of 1.30 (95% CI=1.20-1.41, P for trend < 0.001), 1.47 (95% CI=1.20-1.79, P for trend < 0.001) respectively. The restricted cubic spline curve indicated that NHR had a nonlinear association with all-cause mortality (P for nonlinearity<0.001) and a linear association with cardiovascular mortality (P for nonlinearity = 0.416). Conclusion Our study suggested that elevated NHR was a strong and independent predictor of all-cause and cardiovascular mortality in the general population.